Fidelity, Adaptation, and Meta-commentary: The Case of Susan Orlean’s The Orchid Thief and Spike Jonze’s Adaptation - de ZWAAN, Victoria (Anafora, 2023)
Susan Orlean’s The Orchid Thief has raised and defied questions about genre since its appearance in 1998. Though “research” and “facts” are at the foreground of the book, critics have described it by such terms as literary non-fiction, faction, personal journalism, and non-fiction novel because of its strong “literary,” that is narrative, characterological, thematic, and even philosophical, qualities. Struggling to make a faithful adaptation of this “simple” and “beautiful” book “about flowers” for film, Charlie Kaufman, the neurotic and anxious protagonist/screenwriter of Adaptation (2002), a fictionalized avatar of the real-life Charlie Kaufman, works through the wide range of possible generic and narrative adaptive possibilities that the book invites. The series of apparent false starts eventually get resolved, in a desperate attempt at creating closure, by way of the “Hollywood ending” that the screenwriter ostensibly despises and insists he will avoid. This paper engages the complex relationships between these two objects – The Orchid Thief and Adaptation – first, by providing some interpretive analysis of Orlean’s book and its potential adaptive possibilities, and second, by examining what happens to those possibilities in Adaptation. On my argument, the film refracts the book’s concerns into a meditation on the processes of reading, storytelling, and interpretation in the realm of explicit adaptation by way of metafiction, metalepsis, and other techniques associated with experimental narrative.